Youth Volunteerism's Contribution to Natural Disaster Mitigation in Indonesia: Insights from Muhammadiyah Disaster Management Centre (MDMC) - Subhan Setowara (Jurnal Partisipatoris, 2022)
This research investigates the role of youth volunteerism in mitigating natural disasters in Indonesia, focusing on the experience of the Muhammadiyah Disaster Management Centre (MDMC). The study explores how youth volunteers contribute to disaster response and management efforts, analysing both the strengths and weaknesses of their involvement. It also examines the collaboration between MDMC and Muhammadiyah universities, as well as the engagement of Muhammadiyah Youth, to understand the extent of youth participation in MDMC's initiatives. The study draws on qualitative data, including interviews and document analysis, to gain insights into the impact and effectiveness of youth volunteerism in mitigating natural disasters in Indonesia. The research findings highlight the significant role of volunteer-based disaster relief organizations in Indonesia, considering the country's vulnerability to disasters. The presence of the MDMC is particularly important in supporting sustainable development goals. MDMC effectively collaborates with Muhammadiyah's service units and volunteers to carry out voluntary works. Notably, MDMC actively engages youth volunteers in both disaster response and anticipation efforts.